Biochemical and Taxonomic Characterization of Novel Haloarchaeal Strains and Purification of the Recombinant Halotolerant α-Amylase Discovered in the Isolate - Verma, Dipesh Kumar; Vasudeva, Gunjan; Sidhu, Chandni; Pinnaka, Anil K.; Prasad, Senthil E.; Thakur, Krishan Gopal (Frontiers in Microbiology, 2020)
Haloarchaea are salt-loving archaea and potential source of industrially relevant halotolerant enzymes. In the present study, three reddish-pink, extremely halophilic archaeal strains, namely wsp1 (wsp-water sample Pondicherry), wsp3, and wsp4, were isolated from the Indian Solar saltern. The phylogenetic analysis based on 16S rRNA gene sequences suggests that both wsp3 and wsp4 strains belong to Halogeometricum borinquense while wsp1 is closely related to Haloferax volcanii species. The comparative genomics revealed an open pangenome for both genera investigated here. Whole-genome sequence analysis revealed that these isolates have multiple copies of industrially/biotechnologically important unique genes and enzymes. Among these unique enzymes, for recombinant expression and purification, we selected four putative α-amylases identified in these three isolates. We successfully purified functional halotolerant recombinant Amy2, from wsp1 using pelB signal sequence-based secretion strategy using Escherichia coli as an expression host. This method may prove useful to produce functional haloarchaeal secretory recombinant proteins suitable for commercial or research applications. Biochemical analysis of Amy2 suggests the halotolerant nature of the enzyme having maximum enzymatic activity observed at 1 M NaCl. We also report the isolation and characterization of carotenoids purified from these isolates. This study highlights the presence of several industrially important enzymes in the haloarchaeal strains which may potentially have improved features like stability and salt tolerance suitable for industrial applications.